Effects of noise sourcing on organic memristive devices. (December 2020) - Battistoni, Silvia; Sajapin, Roman; Erokhin, Victor; Verna, Alessio; Cocuzza, Matteo; Marasso, Simone Luigi; Iannotta, Salvatore
Abstract: The effects of noise on any electronic system is a crucial aspect for the delineation of the proper functioning of circuits. Different and consolidated models have been proposed for classical electronic circuital elements but the effect of noise sourcing on memristive devices still lacks a wide and rich experimental description. Despite the larger use of Gaussian white noise in the stimulation of memristive systems, the use of uniform white noise has been recently proposed as a possible method for underlining variations in the impedance of an electronic device and in dynamic monitoring the system evolution. By applying uniform white noise to organic memristive devices (OMDs) while measuring the resulting current noise, we dynamically monitored the effects of noise amplitude on memristive properties. In fact OMDs functioning is based on the interfacial redox activity between polyaniline and a liquid electrolyte and constitutes an intrinsically impedance variation of the channel. We show that noise sourcing affects the hysteresis loops, the typical characteristics of electronic systems endowed with memory.